Surface production operations. Vol. 1, - Arnold, Ken, 1942- (Butterworth-Heinemann, 1999)
"This volume is a thorough, practical reference for specifying, designing, operating and troubleshooting surface production equipment. Focusing on the "why's" as well as the "how's", the authors share their many years of field and classroom experience to give readers a sound basis for understanding and implementing production specifications and management techniques. Both volumes give project engineers, and anyone else who must coordinate and communicate with vendors and detail specialists, important insights into all key areas of surface production operations. Also, each volume contains many example problems that illustrate the latest technology and its applications."-- Description at Knovel site.